Узкополосный фильтр на ПАВ - Лесовая, Н. П.; Бородин, А. В. (ХНУРЕ, 2017)
In recent years, due to the rapid development of mobile originated great interest to the filters, resonators using surface acoustic waves. The main advantage of these filters is the narrow bandwidth, low insertion loss with an acceptable-of-band suppression (25 – 60 dB) and a small dimension. These qualities are very attractive for use in communication systems, filters, in particular in mobile phones. Most of the mobile phones of a number of communication standards as frequency selection components use different types of resonator filters, surface acoustic wave (SAW). To construct a resonator filters used electric, acoustic and combined connection.
Keywords: Узкополосный фильтр; ПАВ